Cytochromes c in Archaea: distribution, maturation, cell architecture, and the special case of Ignicoccus hospitalis - Kletzin, Arnulf; Heimerl, Thomas; Flechsler, Jennifer; van Niftrik, Laura; Rachel, Reinhard; Klingl, Andreas (Frontiers in Microbiology, 2015)
Cytochromes c (Cytc) are widespread electron transfer proteins and important enzymes in the global nitrogen and sulfur cycles. The distribution of Cytc in more than 300 archaeal proteomes deduced from sequence was analyzed with computational methods including pattern and similarity searches, secondary and tertiary structure prediction. 258 predicted Cytc (with single, double or multiple heme c attachment sites) were found in some but not all species of the Desulfurococcales, Thermoproteales, Archaeoglobales, Methanosarcinales, Halobacteriales and in two single-cell genome sequences of the Thermoplasmatales, all of them Cren- or Euryarchaeota. Other archaeal phyla including the Thaumarchaeota are so far free of these proteins. The archaeal Cytc sequences were bundled into 54 clusters of mutual similarity, some of which were specific for Archaea while others had homologs in the bacteria. The cytochrome c maturation system I (CCM) was the only one found. The highest number and variability of cytochromes c were present in those species with known or predicted metal oxidation and/or reduction capabilities. Paradoxical findings were made in the haloarchaea: several cytochromes c had been purified biochemically but corresponding proteins were not found in the proteomes. The results are discussed with emphasis on cell morphologies and envelopes and especially for double-membraned Archaea like Ignicoccus hospitalis. A comparison is made with compartmentalized bacteria such as the Planctomycetes of the Anammox group with a focus on the putative localization and roles of the Cytc and other electron transport proteins.